Key concepts in migration - Bartram, David 1966-; Monforte, Pierre; Poros, Maritsa V. 1968- (Los Angeles SAGE, 2014)
"This book provides lucid and intuitive explanations of the most important migration concepts as used in classrooms, among policymakers, and in popular and academic discourse. Arguing that there is a clear need for a better public understanding of migration, it sets out to clarify the field by exploring relevant concepts in a direct and engaging way [...] It is an ideal resource for undergraduate and post-graduate students studying migration in sociology, politics, development and throughout the social sciences, as well as scholars in the field and practitioners in governmental and non-governmental organizations."
Machine generated contents note 1. Introduction -- 2. Migration -- 3. Acculturation -- 4. Alien/Foreigner -- 5. Assimilation -- 6. Borders -- 7. Brain Drain/Gain/Circulation -- 8. Chain Migration -- 9. Circular Migration -- 10. Citizenship -- 11. Cumulative Causation -- 12. Denizens -- 13. Deportation -- 14. Diaspora -- 15. Displacement and Internally Displaced Persons -- 16. Ethnic Enclaves and Ethnic Economies -- 17. Ethnicity and Ethnic Minorities -- 18. Family Migration and Reunification -- 19. Forced Migration -- 20. Gendered Migration -- 21. Guestworkers -- 22. Human Trafficking and Smuggling -- 23. Integration -- 24. Internal/Domestic Migration -- 25. Labour Migration -- 26. Migrant Networks -- 27. Migration Stocks and Flows -- 28. Multiculturalism -- 29. Refugees and Asylum Seekers -- 30. Regional Integration and Migration -- 31. Remittances -- 32. Restrictionism vs. Open Borders -- 33. Return Migration -- 34. Second Generation -- 35. Selectivity -- 36. Social Capital -- 37. Social Cohesion -- 38. Transnationalism -- 39. Undocumented (Illegal) Migration.
Title from title screen (viewed October 19, 2023)
Includes bibliographical references (pages 149-171)
Description based on MARC record for print version
Keywords: Emigration and immigration